Sinônimo de amar é sofrer? Juventude, violência nas relações íntimas e os processos de subjetivação em uma rede social - Unger, Lynna Gabriella Silva (2017)
In the present study, interested in the interactions of digital social networks and gender violence among young – elected fields as starting points and reflection, we look for understand how the discursive practices about how gender violence are built and the way they operate, especially in the intimacies relationships in order to make visible and re(think) the daily spaces of fight in the production of truths. Therefore, we check about self reports of abusive violence shared in a Facebook group with the purpose of analyze, in the light of Cultural Studies and Gender Studies, articulated to the theoretical-methodological paths based in Foucault, how the subjects means the experienced in their affective-sexual relationships, as well as, built and announce the ways of be and stay in a relationship. Analyzing the speeches which compose this study corpus, we unveil repetitions (in)visible and sayable, sometimes naturalized, building assumed truths by the subjects in their relationships. We highlight the power relationships wich circumscribes such abusive relationships, thei indicate tendeces and enfatizes somo hegemonic pratices. Thus, the discursive pratices annouced unviel that these subjects assume placements that legitimate and reforces the patriarcal culture. Viewing the dynamics of power relationships, especially instated by the gender relationships in intimacies relationships, emerge the necessities of redetermination of senses which have been imprisoning us, for centuries, in a neutralized hegemonic and oppressive conception which pass through the affective-sexual relationships developed nowadays.